PERAN PUSTAKAWAN PERGURUAN TINGGI DALAM MELAKSANAKAN BIMBINGAN LITERASI DIGITAL DI ERA WORK FROM HOME - Andi Saputra (UIN Imam Bonjol Padang, 2020)
This study aims to develop a model of information literacy guidance related to the role of college librarians during the Covid 19 pandemic. The source of the data is obtained by observing the college repository access model, and conducting a library study of students' information literacy abilities in finding reference sources scientific to support the lecture process. Samples were taken from college which were included in cluster 1 of Indonesian college clustering which were released by Kemristekdikti in 2019. The results showed that most of the college repositories still applied limited access and closed access. In addition, the ability of digital literacy of students is still low, even though they are already classified as a native digital generation. This research concludes that the digital literacy learning model that is compiled needs to consider the behavior and habits of the user during their online lectures and learning from home, by utilizing information technology, and social media as a media for publication and promotion.